Cardio‐Selective Beta‐Blocker: Pharmacological Evidence and Their Influence on Exercise Capacity. Issue 2 (26th January 2012) - Ladage, Dennis; Schwinger, Robert H.G.; Brixius, Klara
<x xml:space="preserve">Abstract</x> SUMMARY For the past 40 years, beta‐blockers have been widely used in cardiovascular medicine, reducing morbidity as well as mortality. Beta‐blockers are currently used in a number of cardiovascular conditions such as systolic heart failure, postmyocardial infarction, and in prevention and treatment of arrhythmias. They are not recommended as the first line antihypertensive therapy, particularly in the elderly, unless there are specific indications. Despite the benefits of beta‐blockers, tolerability concerns in patients with co‐morbidities have limited their use. Some of these problems were overcome with the discovery of cardioselective beta‐blockers. The third generation beta‐blockers have additional properties of vasodilatation and advantages in terms of minimizing the adverse effects of beta‐blockers. Some of the advantages include improvement of insulin resistance, decrease in cholesterol as well as alleviation of erectile dysfunction. Acute treatment with beta‐blockers modifies local muscular metabolic properties and impairs endurance exercise capacity whereas the influence of chronic is debated controversially.